(untitled) (Malay Literature, 2025)
The Secondary School Curriculum Framework (KSSM) by the Ministry of Education Malaysia (MOE) is based on six pillars, of which one concerns science and technology. This is intended to encourage students to explore and generate creative ideas as well as to be able to create something innovative. The combination of scientific elements in literary components is also increasingly finding a place amongst short story writers and novelists, which subsequently showcases effective interdisciplinary demonstration in literature. This study was conducted to analyse the elements of science, technology and innovation found in the short story Legasi Tapai Ubi by Ghazali Lateh in the KOMSAS short story anthology titled Bintang Hati. This study attempts to fill the research gap on limited studies connecting elements of science and technology in the short story. This qualitative study involves library research, including a close reading of words, phrases and sentences to identify the elements of science, technology and innovation found in the said short story using a structured observation checklist. The results of the study indicate that the elements of science, technology and innovation feature the themes of medical biotechnology, health science and the use of information technology in research efforts to treat cancer, and this is effectively demonstrated in the short story. The results also present the injection of scientific elements into literature to display the progress of medical technology in treating diseases through creative storytelling. In conclusion, the short story Legasi Tapai Ubi is a literary work that successfully presents interdisciplinary aspects that can be a medium for comprehensive education, inculcating interest in research and innovation, and strengthening food heritage amongst students and the general public. Full text: PDF